2009
DOI: 10.1002/adfm.200801620
|View full text |Cite
|
Sign up to set email alerts
|

Designing a Stable Cathode with Multiple Layers to Improve the Operational Lifetime of Polymer Light‐Emitting Diodes

Abstract: The short device lifetime of blue polymer light‐emitting diodes (PLEDs) is still a bottleneck for commercialization of self‐emissive full‐color displays. Since the cathode in the device has a dominant influence on the device lifetime, a systematic design of the cathode structure is necessary. The operational lifetime of blue PLEDs can be greatly improved by introducing a three‐layer (BaF2/Ca/Al) cathode compared with conventional two‐layer cathodes (BaF2/Al and Ba/Al). Therefore, the roles of the BaF2 and Ca l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…As the BaF 2 thickness increased up to < 3 nm, the series resistance (R s ) tended to decrease, the shunt resistance (R sh ) tended to increase, and thus the FF tended to increase (Table 1). [14] In OLEDs that operate at voltages higher than the V bi of a typical OPV, the device luminous efficiencies did not degrade meaningfully even with much thicker metal fluoride layers (e.g., 8 nm). A BaF 2 layer thicker than a single-coverage layer is an insulator and forms a barrier to electron tunneling.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…As the BaF 2 thickness increased up to < 3 nm, the series resistance (R s ) tended to decrease, the shunt resistance (R sh ) tended to increase, and thus the FF tended to increase (Table 1). [14] In OLEDs that operate at voltages higher than the V bi of a typical OPV, the device luminous efficiencies did not degrade meaningfully even with much thicker metal fluoride layers (e.g., 8 nm). A BaF 2 layer thicker than a single-coverage layer is an insulator and forms a barrier to electron tunneling.…”
Section: Resultsmentioning
confidence: 94%
“…[14] In OLEDs that operate at voltages higher than the V bi of a typical OPV, the device luminous efficiencies did not degrade meaningfully even with much thicker metal fluoride layers (e.g., 8 nm). [14,16] The grain size of BaF 2 tended to increase as the deposited nominal thickness increased as monitored by using a quartz crystal microbalance sensor. Although the V oc was still high in the device with a BaF 2 layer thicker than a single-coverage layer, the insulating nature of BaF 2 and electron accumulation at the interface because of the blockage of extraction increased the R s from 11.7 W cm 2 at 3 nm to 30.9 W cm 2 for a 5 nm BaF 2 interfacial layer and thus reduced the FF, which caused the S-shaped J-V behavior in the device with a 5 nm thickness (Figure 1 a).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…[7][8][9][10] Many researchers have studied the electron injection from cathodes to organic layers. [11][12][13][14] Most of the light-emitting polymers, including a poly(9,9 0 -dioctylfluorene) (PDOF) [15][16][17][18][19] that is known as a good blue lightemitting polymer, have barriers of electron injection because of their low work functions. Therefore, a low work function metal such as calcium has been used as a cathode material to reduce the barriers.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a low work function metal such as calcium has been used as a cathode material to reduce the barriers. 11,13,18) Another way to enhance the electron injection at the cathode/polymer interface is modification of the interfacial structures. [20][21][22] It is suggested that interfacial structures such as a polymer orientation, cluster formation of metals, and interface adhesion strongly affect the device properties.…”
Section: Introductionmentioning
confidence: 99%